Essence and constitution in Zubiri - Fernández, Alfonso Gómez (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The aim of this article is to expound Zubiri’s concept of essence and to begin a critical discussion and evaluation of his proposal. Before explaining what essence is, it is necessary to observe that, for our author, not all things have an essence: only «reality-things» but not «meaning-things» form part of the «essentiable domain». This distinction between «reality-things» and «meaning-things» supposes a new conception of nature. (Nature is not the opposite of the artificial, as the Greek term physis is.)«Reality-things» form a constitutional and «closed» system of non-causal and non-«external» characteristics or traits. These «foundational characteristics» of constitution, then, are precisely the essence. The article discusses critically the assumptions of this doctrine (reality, ontological pluralism, foundation) and its possible limits in the light of contemporary science. It can be a useful theory for the philosophy of language.